Injection port silylation of γ-hydroxybutyrate and trans-hydroxycrotonic acid: Conditions optimisation and characterisation of the di-tert-butyldimethylsilyl derivatives by GC-MS - Elie, Mathieu Pierre; Baron, Mark G; Birkett, Jason W (Analyst (London), 2012)
Silylation is usually carried out on γ-hydroxybutyrate (GHB) for its analysis by Gas Chromatography/Mass Spectrometry (GCMS) and requires potentially long incubation times before injection during which the derivatisation reagent and derivatives (such as trimethyl-silyl compounds) can hydrolyse. Moreover, alternative internal standards (IS) are often useful depending on sample matrices, extraction/purification procedures, commercial availability and price. This study evaluated the possibility of silylating GHB with an injection port derivatisation procedure using N -methyl- N -[ tert -butyldimethyl-silyl]trifluoroacetimide (MTBSTFA) with 1% tert -butyldimethylchlorosilane (TBCS) as the derivatisation reagent, producing di- tert -butyldimethyl-silyl derivatives as a novel means of analyzing GHB. In parallel, trans -hydroxycrotonic acid ( t -HCA) was investigated as a potential IS for GHB quantification. Analyses were carried out with a temperature programmable injector and the GHB( t -BDMS) 2 and t -HCA( t -BDMS) 2 derivatives were successfully produced, characterised and derivatisation conditions optimised. t -HCA behaved very similarly to GHB through the derivatisation processes and was used as the IS for the determination of urinary endogenous GHB concentrations in human subjects where the method showed a limit of detection of 0.049 μg mL −1 , a limit of quantification of 0.162 μg mL −1 , and a limit of confirmation of 1.33 μg mL −1 , suitable for toxicological GHB concentration determination. A GC-MS temperature programmable injector was used to control and optimise the direct in-port silylation of GHB and t -HCA (novel IS). Urinary endogenous GHB concentration determination proved the method appropriate for the toxicological analysis of GHB.